Developmental abnormalities of Bettasplendens embryos reared in oil and grease contaminated water samples of Vavuniya reservoir, Sri Lanka - Umasuthan, S.; Patrick, A.E.S.; Naveendrakumar, G.; Kuganathan, S. (University of Jaffna, 2017)
In Vavuniya urban area the wash-outs from petroleum automobile service stations contain Kerosene oil, lubricating engine oil, grease as major compounds that contributing oil and grease pollution in Vavuniya reservoir, Sri Lanka. To investigate the potential oil and grease toxicity on fish embryo development, the Bettasplendens (Siamese fighting fish) embryos were reared in water samples from Vavuniya reservoir. Average value of oil and grease content from polluted location was determined for the preparation of artificial aliquots of oil and grease (20 mg of Engine oil: Kerosene oil: Grease =1:1:1 w/w). These aliquots mixed with the 1000 ml of water samples obtained from non- polluted location of this reservoir. Prepared medium was shaken vigorously for 5 minutes and 25ml was added in each Petridish to prepare the larval growth medium. Meantime, 25ml of non-polluted water was taken in another set of Petri dishes as a control setup. Treatments and control were allowed under natural diffuse photo periods. Frequent microscopic examinations were done until 72hpf (hours post-fertilization) for embryological abnormalities and compared with control group from March to December2016. Significant embryo developmental abnormalities such as delayed and reduced outgrowth of the caudal fin-fold (p= .008) reduction in melanin pigment formation (p= .04) and higher larval mortality (75 %) were observed. Hence, much higher potential of oil and grease impacts on fish embryo development observed in this study, suggests the threats for survival of local fish species in Vavuniya reservoir. Assessment of oil and grease impact on the reproductive potential of the local fish species is necessary for its conservation in their natural habitats
Keywords: Developmental abnormalities; Oil; grease pollution